Sporotrichosis in Rio de Janeiro, Brazil: Sporothrix brasiliensis is associated with atypical clinical presentations. - Rodrigo Almeida-Paes; Manoel Marques Evangelista de Oliveira; Dayvison Francis Saraiva Freitas; Antônio Carlos Francesconi do Valle; Rosely Maria Zancopé-Oliveira; Maria Clara Gutierrez-Galhardo (Public Library of Science (PLoS), 2014)
There have been several recent changes in the taxonomy of Sporothrix schenckii as well as new observations regarding the clinical aspects of sporotrichosis. In this study, we determined the identification of the Sporothrix species associated with both classic and unusual clinical aspects of sporotrichosis observed in the endemic area of sporotrichosis in Rio de Janeiro, Brazil.To verify whether S. brasiliensis is associated with clinical manifestations of sporotrichosis, a cross-sectional study was performed in which Sporothrix isolates from 50 patients with different clinical manifestations were analyzed and their isolates were studied by phenotypic and genotypic methods. Data from these patients revealed a distinct clinical picture and therapeutic response in infections caused by Sporothrix brasiliensis (n = 45) compared to patients with S. schenckii sensu stricto (n = 5). S. brasiliensis was associated with disseminated cutaneous infection without underlying disease, hypersensitivity reactions, and mucosal infection, whereas patients with S. schenckii presented with less severe and more often localized disease, similar to the majority of previously described sporotrichosis cases. Interestingly, S. brasiliensis-infected patients overall required shorter durations of itraconazole (median 16 weeks) compared to the individuals with S. schenckii (median 24 weeks).These findings suggest that Sporothrix species are linked to different clinical manifestations of sporotrichosis and that S. brasiliensis is effectively treated with oral itraconazole.